2018
DOI: 10.1071/ah17082
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrition programs for Aboriginal and Torres Strait Islander Australians: an overview of systematic reviews

Abstract: To provide an overview of previous reviews of programs that aimed to improve nutritional status or diet-related health outcomes for Aboriginal and Torres Strait Islander peoples, in order to determine what programs are effective and why. A systematic search of databases and relevant websites was undertaken to identify reviews of nutrition interventions for Aboriginal and Torres Strait Islander Australians. Pairs of reviewers undertook study selection and data extraction and performed quality assessment using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…Programmes and policies to promote nutrition should draw on the strengths of Indigenous families and communities, and must be conducted in partnership with Indigenous communities and individuals ( 24 , 88 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Programmes and policies to promote nutrition should draw on the strengths of Indigenous families and communities, and must be conducted in partnership with Indigenous communities and individuals ( 24 , 88 ) .…”
Section: Discussionmentioning
confidence: 99%
“…All of these diseases necessitate the importance of effective nutrition interventions early in childhood, with schools an obvious setting. While the evidence for effective Aboriginal nutrition interventions is not strong, a review has found that community-based programs that engage and are led by members of the Aboriginal community and incorporate multiple components are most effective [50]. How best to involve Aboriginal parents and volunteers in SBPs needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of Aboriginal food and nutrition programs, Browne and colleagues (2018) conclude that “the most important factor determining success of Aboriginal and Torres Strait Islander food and nutrition programs is community involvement in (and ideally, control of) program development and implementation” [50]. As further argued by Bramwell et al (2017), “given the sensitivity and shame often associated with food insecurity, more needs to be known about how health professionals can broach the issue to ensure dignity and cultural safety” ([48] p. 7).…”
Section: Discussionmentioning
confidence: 99%